Conduct disorder and behavioural parent training : research and practice - O'Reilly, Dermot, 1956- (Jessica Kingsley Publishers, 2005)
'An excellent, scholarly, but essentially practical book. Salut+. One to keep at your elbow.'. - from the Foreword by Professor Brian Sheldon. Progress made with children with conduct disorder in specialist schools often does not transfer to the home, but this book shows how behavioural parent training and applied behaviour analysis can help professionals work with parents to continue improving their child's behaviour. Conduct Disorder and Behavioural Parent Training provides a comprehensive introduction to the field of conduct disorder and the individual, familial and social factors that inf.